A Study about Consumer Attitude towards Online Grocery Stores - Arora, Divya; Gupta, Sudipta Sen (Gyan Management Journal, 2022)
Online grocery shopping has grown rapidly over the past few years. The purpose of this research is able to identify the concept of online grocery stores and to understand how the consumer feels about purchasing groceries from these online stores, also this paper is about determining the elements that might encourage or oppose consumers to purchase groceries from online stores. Basically, how consumers perceive online grocery stores. The findings would emphasize consumer attitudes towards online grocery stores and how online grocery shopping changes consumer behaviour and shopping pattern.